1939
DOI: 10.1002/zaac.19392420307
|View full text |Cite
|
Sign up to set email alerts
|

Kristallstruktur und magnetisches Verhalten des metallischen Holmiums

Abstract: 1. Holmium kristallisiert in hexagonal dichter Packung mit den Achsen a = 3,557 und c = 5,620.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

1941
1941
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…Work was performed in the Ames Laboratory of the U.S. Atomic Energy Commission. ~f Bommer, 1939a;Meisel, 1939. ++ Bommer, 1939aQuill, 1932a, b.…”
Section: Sample Preparation and Equipmentmentioning
confidence: 99%
“…Work was performed in the Ames Laboratory of the U.S. Atomic Energy Commission. ~f Bommer, 1939a;Meisel, 1939. ++ Bommer, 1939aQuill, 1932a, b.…”
Section: Sample Preparation and Equipmentmentioning
confidence: 99%
“…Europium has been characterized by several workers (3,13) as divalent in the metallic state. This is again borne out by the isomer shift of the metal, which is clearly much closer to that of the covalent divalent compounds than that of the covalent trivalent compounds.…”
Section: "Valence" In the Metallic Statementioning
confidence: 99%
“…In 1937 (4) and 1939 (5), Klernin and Bommer studied the paramagnetic sus ceptibility of gadolinium, terbium, dysprosium, holmium, and erbium and found that the susceptibility was large in all cases and that they all had paramagnetic Curie temperatures between 0°K and room temperature.…”
mentioning
confidence: 99%
“…so that the saturation magnetization, according to Equation 1-1 is given by M = NgJug . (1)(2)(3)(4)(5)(6)(7)(8) Here, the effective number of Bohr magnetons is M-eff ~ gJ • (1--9) This corresponds to the situation where the spins of all the ions are parallel and in this regard is equivalent to the ferromagnetic case.…”
mentioning
confidence: 99%
See 1 more Smart Citation